Low-titer group O whole blood: challenges to blood stations - LIN Hong; YU Xi; HU Wenjia; MA Ling (Zhongguo shuxue zazhi, 2025)
Whole blood transfusion for the resuscitation of trauma patients is not a new concept, with its history dating back to World War I. Due to the significant survival benefits of early intervention with whole blood, an increasing number of countries and regions are using whole blood for pre-hospital resuscitation of patients with traumatic haemorrhage. Whole blood containing low-titer anti-A and anti-B antibodies is known as low-titer group O whole blood. The safety of transfusion of low-titer group O whole blood has been proven in military and local trauma centers in some countries. The use of low-titer group O whole blood for pre-hospital trauma care in China will pose new challenges to blood stations that provide whole blood. This paper reviews the selection of group O donors, the setting of anti-A and anti-B titers threshold and their detection, as well as the collection, preparation and storage of whole blood.